2021
DOI: 10.1016/j.afjem.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in trauma according to alcohol sale restrictions during the South African national COVID-19 lockdown

Abstract: Introduction The South African government enforced various alcohol sale restrictions during the COVID-19 lockdown in order to reduce hospital admissions related to alcohol-associated injuries. A cross-sectional study was performed to describe the temporal changes in trauma according to alcohol sale restrictions during the South African national COVID-19 lockdown. Methods Data from all trauma-related patients presenting to the emergency centre of Mitchells Plain Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…We collected infections within the first 7 days only in the pilot, which will need to be extended to the entire hospital course during the main study. In addition, it is plausible that the local public health measures and resulting societal changes, during the early waves of the COVID-19 pandemic in 2020, resulted in less infective mechanisms of wounding such as community assaults—van Hoving et al 44 showed that there were fewer open wounds during periods of alcohol bans during COVID-19 at one of the pilot hospitals. Another reason could be that lower patient volumes may have enabled earlier infection control measures 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected infections within the first 7 days only in the pilot, which will need to be extended to the entire hospital course during the main study. In addition, it is plausible that the local public health measures and resulting societal changes, during the early waves of the COVID-19 pandemic in 2020, resulted in less infective mechanisms of wounding such as community assaults—van Hoving et al 44 showed that there were fewer open wounds during periods of alcohol bans during COVID-19 at one of the pilot hospitals. Another reason could be that lower patient volumes may have enabled earlier infection control measures 43 .…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] However, a more likely reason for low proportion of CRIs is the change in local trauma epidemiology consequent to the COVID-19 pandemic. 43,44 There were two main effects attributed to local alcohol bans, lockdown periods, and public curfews: fewer than usual trauma cases, and lower injury severity and fewer trauma deaths. 43,44 Prepandemic, the trauma mortality rate was around 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Alcohol-ban initiatives have shown promise in reducing trauma admissions from interpersonal violence. 32,33 Additionally, South Africa's Firearm Control Act has reduced firearm-and nonfirearm-related homicides. 34 However, more widespread interpersonal violence prevention initiatives targeting men are needed, as men are both the most common perpetrators and victims.…”
Section: Discussionmentioning
confidence: 99%
“…Urban upgrading through infrastructural intervention has been shown to reduce the risk of interpersonal violence in the poorest and most violent townships of Cape Town 31 . Alcohol‐ban initiatives have shown promise in reducing trauma admissions from interpersonal violence 32,33 . Additionally, South Africa's Firearm Control Act has reduced firearm‐ and non‐firearm‐related homicides 34 .…”
Section: Discussionmentioning
confidence: 99%